Особливості радіобіологічного впливу на процеси обміну колагену в УЛНА на ЧАЕС залежно від типів структурно-геометричного ремоделювання міокарда за метаболічного синдрому - Муравйова, І. М.; Коваленко, О. М. (Clinical Endocrinology and Endocrine Surgery, 2008)
We investigated the association of collagen type I turnover in ChNPP accident clean-up work ers with metabolic syndrome, intercommunication with possible dose response dependencies and contribution to enhancement of myocardial fibrosis according to types of myocardial remodeling. Maine group subdivided into 2 subgroups: 50 patients exposed with doses over 1 Gy, 50 patients up to 1 Gy; 37 no exposed patients in control group. The amino terminal propeptide of procol lagen type I (PINP) and carboxy terminal telopeptide of collagen type I (ICTP) were measured by radioimmunoassay in serum samples. All participants underwent echocardiography, assessed Systematic Coronary Risk Evaluation (SCORE), interstitial collagen volume fraction. PINP level was greater in ChNPP accident clean-up workers with concentric hypertrophy cardiac remodeling (p<0.05) and linear dependence was present with SCORE (r=0.47, p<0.05). More evident left ventricular configuration abnormality in ChNPP accident clean up workers were presented by thickness wall and cavity linear-volume size. Parameters of left ventricle posterior wall thickness and end diastolic volume could be used to estimate of intensity myocardial fibrosis in depends on absorbed doses external irradiation and independently of model geometric remodeling.